PERAN PEMERINTAH DAERAH PROVINSI RIAU DALAM PENGELOLAAN DAS SIAK: STUDI KASUS DAERAH HILIR DAS SIAK TAHUN 2010-2013 - Lestari, Reski; Ridwan, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This reseacrh is aimed to figure out how is the role of Riau Province Local Governmenton Siak Watershed Management (known as Daerah Aliran Sungai, DAS). It is focused to thedownstream watershed of Siak River area considering to the most complex problem exists on it.Those problems consist of domestic waste, industry waste, residential issue. The role of localgovernment on DAS management especially for downstream area is based on main duty and thefunction of each related government Departement. On this management there are no specificregulation in DAS management area. Based on this background, the research is aimed toanalyze the role of Local Government in the Province of Riau on DAS management that isfocused on the downstream of DAS.The type of this reseacrh is description, which means the researcher gives a descriptionor illustration about related phenomenon or social symptom which is analyzed by describingindependent variable systematicly and accurately. Data collection method is done by IndepthInterview and documnetation study.The result of analysis shows that the role of local government on DAS management ofdownstream is based on “TUPOKSI (Tugas Pokok dan Fungsi)” of each Departement.Departement of Living Environment (known as Badan Lingkungan Hidup, BLH) has a role onmanaging industry waste, domestic waste, Departement of Public Project (known as DinasPekerja Umum, PU) Riau Province Resicence Division has a role on resident management.While cooperation of each Departement is needed on DAS management.Keywords: Role, Local Government, River Stream District